SPECIFIC FEATURES OF HISTORICAL AND GEOGRAPHICAL POSITION OF VERHNEOKSKIY AREA IN THE MIDDLE XIX CENTURY (ON MATERIALS OF THE ORYOL PROVINCE) - Nikolai Zhirov (Гуманитарные и юридические исследования)
The article gives a comparative analysis of dynamics as regards major natural resources in the upper reaches of the Oka river in the Oryol province during the first half of the XIX century. The topic under consideration is poorly studied so far. Military statistics digests served the main source of material as they provide objective and reliable data on geographic peculiarities of the region and its economic development. A comprehensive study of the sources was conducted with the use of both traditional scientific methods (system and retrospective analyses, structural approach) and modern approaches (civilizational approach, mathematical statistics method). The correlation of natural аnd anthropogenic factors in the agricultural community development in the south of Central Russia in abovementioned period was identified by the example of the Oryol province. The study highlights that thereduction of land allotment in the Oryol province did not breach the ecological niche in the first half of the XIX century. But further involvement of forest and grassland in agricultural use threatened with an imminent soil degradation and as a consequence entailed an environmental and socio-economic crisis in the region.